2018
DOI: 10.1139/cjc-2017-0526
|View full text |Cite
|
Sign up to set email alerts
|

Facile preparation and isolation of neutral organic electron donors based on 4-dimethylaminopyridine

Abstract: A number of new neutral bis-2-(4-dimethylamino)pyridinylidene electron donors featuring N-akyl groups of varying lengths (propyl, butyl, hexyl, dodecyl) have been prepared from 4-dimethylaminopyridine by means of a simple two-step procedure. Each derivative could be isolated in high yield and could be stored indefinitely under inert atmosphere. The electron donors were chemically oxidized to the corresponding bipyridinium ions, and all compounds were characterized by NMR spectroscopy and cyclic voltammetry. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Despite the fact that MeCN is the most widely used solvent for non-aqueous organic RFBs owing to its high ionic conductivity and low viscosity, 16,52 it was felt that DMF would be a better alternative for BPY 2. Indeed, DMF-based electrolytes are most commonly used in assessing the redox potential of the 2/2 2+ couple and that of related compounds, [42][43][44]53 and a related N,N′-dimethyl derivative appears to have poorer reversibility in MeCN 54 than in DMF. 42 In terms of a supporting salt, we chose NaBF 4 which is low cost and has a low molecular weight.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the fact that MeCN is the most widely used solvent for non-aqueous organic RFBs owing to its high ionic conductivity and low viscosity, 16,52 it was felt that DMF would be a better alternative for BPY 2. Indeed, DMF-based electrolytes are most commonly used in assessing the redox potential of the 2/2 2+ couple and that of related compounds, [42][43][44]53 and a related N,N′-dimethyl derivative appears to have poorer reversibility in MeCN 54 than in DMF. 42 In terms of a supporting salt, we chose NaBF 4 which is low cost and has a low molecular weight.…”
Section: Resultsmentioning
confidence: 99%
“…Although various bispyridinylidene derivatives have been isolated, [40,52] they are most conveniently generated in situ owing to their extreme air‐sensitivity [8] . In our hands, attempts to isolate 3PhCy , 3CyPh and 3CyCy in pure form were not successful.…”
Section: Resultsmentioning
confidence: 87%
“…It is worth noting that the assignment of signals to the E and Z isomer (Table 3) for 3PhCy and 3CyPh are based on the observed preference of Z over E isomers determined for 3PhPh , [40] and also found for derivatives 2 a , and 2 c–d [38,52] . For 3CyCy , which showed a 1 : 1 ratio of isomers, 1 H NMR signals were definitively assigned to E and Z isomers using a ROESY NMR experiment (see Figure S1 in the Supporting Information), while the 31 P chemical shifts of the isomers were assigned by comparison to the shifts of the Cy 3 P=N− groups in the positions ortho and para to the pyridyl N‐CH 3 of 3PhCy and 3CyPh , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, thiazol-2-ylidenes have been postulated as single-electron donors in their own rights, and therefore as rare examples of organic reductants. However, a recent report by Martin, Tomás-Mendivil et al showed that during the reaction, the thiazol-2-ylidenes dimerize leading to the corresponding electron-rich olefins, a class of compounds which have already been demonstrated as potent organic reductants . Regardless of this issue, the question remains whether a stable singlet carbene could act as an organic reducing agent.…”
mentioning
confidence: 99%